STUDI ANALISIS JAMINAN KEMATIAN (JKM) BAGI APARATUR SIPIL NEGARA SEBAGAI WARISAN BESERTA KONSEKUENSINYA DALAM ISLAM - Nisa, Rifqi Zahratun; Syamsuddin, S; Baehaqi, B (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
Inheritance is a matter that’s closely related to the scope of human life, and becomes a tradition without knowing the limits of time or place, considering that all humans will inevitably experience death. Among the sources of property that exist today is the Death Insurance (Jaminan Kematian (JKM)) for State Civil Apparatus (Aparatur Sipil Negara (ASN)) which is handed over to the heirs of the deceased ASN and managed in accordance with applicable laws and regulations. This study aims to analyze whether Jamian Kematian (JKM) for civil servants is included in the category of inheritance according to Islamic jurisprudence and the consequences that exist from the results of the analysis. This research is a qualitative descriptive research that collects Jaminan Kematian (JKM) data for civil servants with a clear picture in the form of words. In order to collect data in this study, direct research, interviews, and documentation studies were used. Data analysis techniques in this study use normative approaches, inductive thinking, and peer examination. The conclusion that can be drawn from this study is that Jaminan Kematian (JKM) is not included in the definition of inheritance according to Islam, as for the consequences of the results of the study, Jaminan Kematian (JKM) must be distributed to heirs in accordance with applicable laws and regulations.